Omentin-1 Ameliorated Free Fatty Acid-Induced Impairment in Proliferation, Migration, and Inflammatory States of HUVECs - Yubin Chen; Fen Liu; Fei Han; Lizhi Lv; Can-e Tang; Fanyan Luo (Cardiology Research and Practice)
Objectives. Endothelial cell injury is a critical pathological change during the development of atherosclerosis. Here, we explored the effect of omentin-1 on free fatty acid- (FFA-) induced endothelial cell injury. Methods. An FFA-induced endothelial cell injury model was established to investigate the role of omentin-1 in this process. Cell proliferation was analyzed with the Cell Counting Kit assay and flow cytometry. Scratch and transwell assays were used to evaluate cell migration. Factors secreted by endothelial cells after injury were detected by western blotting, reverse-transcription quantitative polymerase chain reaction, and cellular fluorescence assay. Results. Omentin-1 rescued the FFA-induced impaired proliferation and migration capabilities of human umbilical vein endothelial cells (HUVECs). It decreased the number of THP-1 cells attached to HUVECs in response to injury and inhibited the FFA-induced proinflammatory state of HUVECs. Conclusion. Omentin-1 could partly ameliorate FFA-induced endothelial cell injury.